The Role of School Principal’s Transformational Leadership in Achieving Quality Education - Qoribah, Siti; Nurdin, Diding; Suryadi, Suryadi (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study aims to analyze the implementation of transformational leadership by the principal in enhancing the quality of educational services at Early Childhood Education Imanda. Employing a qualitative approach with a case study method, data were collected through observations, in-depth interviews, and documentation. The findings reveal that the principal applies the four dimensions of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The application of this leadership style positively impacts teacher motivation, innovation in learning, and parental satisfaction with educational services. The study concludes that transformational leadership is effective as a strategy for improving the quality of early childhood education services. These findings contribute to the development of educational management practices at the early childhood education level.​